P-BN52 Patient-reported outcome measures following fundoplication – lind and nissens - single centre, single surgeon results. (16th December 2021) - Muthusami, Anitha; Jayaprakash, Sindoora; Jangan, Akash; Sellahewa, Chaminda; Akingboye, Akinfemi
Abstract: Background: Gastro-oesophageal reflux disease (GORD) affects approximately 10%-20% of adults in Western Countries. Surgery is indicated following failed medical therapy. This is recommended when GORD symptoms have a significant impact on the quality of life (QOL). A long term follow up is critical to authenticate outcomes following anti-reflux/hiatal hernia repair surgery. Objective information must be linked to the patient's perception of the disease and the impact on the QOL. Our survey aims assess the long term patient's satisfaction and the impact on QOL following standard Nissen's and Lind's fundoplication for GORD. Methods: A single surgeon's prospective database of laparoscopic and or open hiatus hernia repair and fundoplication with patient's demographics since 2014 in a district general hospital was analyzed. These patients were contacted virtually between June and July 2021. Verbal consent was obtained,  the patients were asked to answer questions from the GERD HRQL (AUGIS modified for use in National Hiatal Surgery Registry) for Hiatus Hernia (HH) or Gastro-oesophageal reflux disease (GORD) or both to assess postoperative symptoms relief, complications, and overall quality of life. The scoring scale was divided into two categories; no symptoms or mild–moderate symptom improvement and those with significant symptoms. Results: Of the 93 patients, 85 (91.4%) underwent primary laparoscopic repair with 91 cases performed as elective procedure. 68 patients (73%) underwent a Lind wrap, 24 (26%) had a floppy Nissen's and one was a dor procedure. Three patients with unrelated death were excluded from the analysis. We had 67 responders (74.4%), 56 answered the GORD questionnaire and 66 responded to the HH questionnaire.  84% patients with GORD and 85% of patients with HH had significant symptom improvement. 61 % and 55% suffered from significant gas bloat symptoms in each group. As for dysphagia; 77% had no - mild dysphagia and 23% had significant dysphagia and this was 79% and 21% in HH group.  Conclusions: Overall patients satisfaction and improvement in quality of life was 90% . Half of our patient experienced gas bloat syndrome, which had little effect on their quality of life. 20% had long term dysphagia and one third of the patients seem to continue to use PPI despite expressing a satisfactory clinical improvement. It appears that patient's long term improvement on  the   quality of life was satisfactory from both Nissen's and Lind procedure.